THE INFLUENCE OF BRAND AWARENESS, TRANSACTION FEES ON CONSUMER INTENTION IN TRANSACTING USING ATM OFF NETWORK/OFF US WITH CONSUMER TRUST AS A MODERATING VARIABLE - Ali Andri (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2024)
The banking industry in Indonesia is growing rapidly. To stay competitive, banks are expanding their service channels, including ATMs’ services. While crucial terminals for bank-customer interactions, (such as cash withdrawals, fund transfers, bill payments, and more) ATMs require significant investment in both equipment and operational costs. Moreover, deployment of ATM machines carrie risks. One of which is choosing poorly located sites. This study aims to examine factors affecting public transactions at off-us ATMs, also known as Multi Acquiring ATMs, and to measure the impact of brand awareness and transaction costs on customer intention in using these services, with consumer trust as a moderating variable. This study finds that brand awareness positively impacts on off us ATMs’ customer intention, while higher transaction costs result in lower intention. Furthermore, customer trust on the brand is proven to have a moderating impact both on the brand awareness and transaction cost relationships to customer intention